Can Participation Be Induced? Some Evidence from Developing Countries - Mansuri, Ghazala; Rao, Vijayendra (Taylor and Francis, 2013)
Influenced by Amartya Sen, over the last decade, The World Bank has allocated nearly US$80 billion to local participatory development projects targeting poverty, improved public service delivery, and strengthened social cohesion and government accountability. But the success of these programs is hindered by both endogenous local factors and flawed program design and implementation. Two especially important local obstacles are (1) entrenched interests of political agents, civil bureaucrats, and non-governmental organizations (NGOs) with either incentives to resist or capabilities to appropriate program resources, and (2) poverty and illiteracy, as the poor and illiterate participate less and benefit less from participatory projects than do the wealthier, more educated, and more connected. After reviewing hundreds of participatory projects, three lessons are clear for program planning. First, contextual factors like inequality, history, geography, and political systems (among others) are important. Second, communities do not necessarily have a ready stock of ‘social capital’ to mobilize. Third, induced participatory interventions work best when supported by a responsive state – donors cannot substitute for a non-functional state, and successful programs combine enlightened state action from above with social mobilization from below. Future participatory development projects would benefit substantially from revised planning and considerably more attention paid to evaluation and monitoring. Project managers have historically paid little attention to context, monitoring, or evaluation, in part because The World Bank’s operational policies did not provide incentives to do so. Donor agencies should also exercise greater patience and allow for flexible, long-term engagement to facilitate contextual and programmatic learning, including learning from failure.